Rapidly Progressive Radiation Dermatitis in a Liver Transplant Patient Using Tacrolimus-Based Immunosuppression - Akovalı, Emine Sedef; Şahin, Merve; Çolpan Öksüz, Didem (Cerrahpaşa Medical Journal, 2025)
Cite this article as: Akovalı ES, Şahin M, Öksüz DÇ. Rapidly progressive radiation dermatitis in a liver transplant patient using tacrolimus-based immunosuppression. Cerrahpaşa Med J. 2025, 49, 0021, doi:10.5152/cjm.2025.25021.